Human Resources Availability and Input for Effective Administration of Secondary Schools in Ondo West, Nigeria - Iluyemi, Akinniranye Oluwarotimi; Afolake, Edafiogho Oluwatoyin (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The success of educational management depends heavily on the availability and quality of human resources (HR). However, in Ondo West, Nigeria, the effectiveness of secondary school administration is often hampered by issues of staff adequacy and the quality of available HR input. Therefore, this study aims to investigate the availability of human resources and its contribution to the effectiveness of secondary school administration in Ondo West, Ondo State, Nigeria. This study employed a descriptive survey research design. The study population included school principals, vice principals, and Ministry of Education personnel. A sample of 120 respondents was selected using a purposive sampling technique. The research instrument was a self-administered questionnaire (QHRAIEASSOWOSN) with a 4-point Likert scale. The instrument's validity was tested by a measurement expert, while its reliability achieved a coefficient of 0.67 through a test-retest method. Data was analyzed using mean scores, standard deviations, frequencies, and simple percentages. The research shows that obtaining human resources is difficult, even though they are abundant. The survey found that Ondo West secondary schools are understaffed. The number of available staff does not match school administration’s needs for best effectiveness. This study contributes to the literature on teacher-student ratios and administrative staff in educational management. Based on these findings, the government and education providers should prioritize hiring new staff, improving staff quality through human resource development training, and staffing schools proportionally to student enrollment to improve administration.